1971
DOI: 10.1063/1.1674603
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectra, Dipole Moments, and Torsional Potential Constants of cis- and trans-Cyclopropanecarboxylic Acid Fluoride

Abstract: Articles you may be interested inThe theoretical prediction of infrared spectra of trans-and cis-hydroxycarbene calculated using full dimensional ab initio potential energy and dipole moment surfaces Microwave spectra have been assigned for the ground state and several excited torsional states of species of cyclopropa~ecarboxylic ac!d fluoride with the oxygen atom cis and trans to the cyclopropane ring. Dipole moments obtamed by analysIs of the Stark effect are as follows: trans species: J.la=3.43±0.03 D, J.lb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 9 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Conformational properties of substituted cyclopropanes have interested chemists for a long time. It has been shown that the preferred forms of cyclopropane derivatives, which contain substituents with unsaturated groups such as CHO, 1 CFO, 2 CClO, 3 COOH, 4 CHdCH 2 , 5 and NO 2 , 6 have a symmetry plane (C s symmetry), with the substituent lying in this plane. A different conformational preference is observed for cyclopropanols.…”
Section: Introductionmentioning
confidence: 99%
“…Conformational properties of substituted cyclopropanes have interested chemists for a long time. It has been shown that the preferred forms of cyclopropane derivatives, which contain substituents with unsaturated groups such as CHO, 1 CFO, 2 CClO, 3 COOH, 4 CHdCH 2 , 5 and NO 2 , 6 have a symmetry plane (C s symmetry), with the substituent lying in this plane. A different conformational preference is observed for cyclopropanols.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of this ring is a complicating factor that is likely to have interesting conformational consequences. In cyclopropane derivatives with unsaturated substituents such as CHO, CFO, CClO, CO 2 H, vinyl, or nitro, the most stable conformations are those with the plane of the substituent in the symmetry plane of the molecule. CC−C−O syn form(s) are thus expected for ECP when this compound is regarded as a cyclopropyl derivative with an unsaturated substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the three cyclopropylcarbonyl halides (X = F, Cl, Br) consist of predominately cis conformers with less stable trans conformers also present in the fluid states. 7,8 On the other hand, however, the trans conformer has been determined to be more stable for the cyclopropylsubstituted ethenes that have been studied. Vinylcyclopropane has been the subject of a number of exhaustive studies,5,9 but the latest study by Carreira et al appears to be the most definitive.…”
Section: Introductionmentioning
confidence: 99%